THE EFFECT OF RETURN OF RECEIVABLES ON PROFITABILITY IN FINANCING INSTITUTION SECTOR COMPANY REGISTERD ON THE IDX 2013-2017 - Lorina Siregar Sudjiman; Paul Eduard Sudjiman (Fakultas Ekonomi Universitas Advent Indonesia, 2019)
This study aims to investigate the effect of return on receivables on profitability in the Financing Institution Sector Services Company listed in Indonesia Stock Exchange (IDX) in 2013-2017. The population used in this study is the Financing Institution Sector Services Company Registered on the Stock Exchange in 2013-2017. The research sample was taken by purposive sampling, so that there are 7 (seven) companies that meet the sampling criteria in the Financing Institution Sector Services Company Registered on the IDX. Data Collection Techniques Data used in this study are secondary data, namely in the form of financial report data sourced from the Indonesia Stock Exchange in 2013-2017. The data source of this research was obtained from the internet through the official website of the Indonesia Stock Exchange (IDX), namely Indonesia Stock Exchange (IDX) www.idx.co.id, in the form of the company's financial statement data from 2013-2017. Data Analysis Techniques in this study, the author uses Data Regression analysis. Based on the results of statistical analysis by the author, the Receivable Turnover correlation coefficient to Profitability has a significant effect between receivable turnover to profitability seen from the value r = 0.449, Significant value 0.01 <0.05. The coefficient of determination which shows R square = 0.068, which means that the number shows the contribution of accounts receivable turnover factors to profitability of 20.1% while 79.9% is influenced by other factors not examined in this study.